A blade element momentum model for dual-rotor wind turbines considering inter-rotor velocity interferences. Issue 4 (1st May 2022) - Yin, F F; Chen, J J; Li, X K; Ye, Z L; Tang, W; Shen, X; Guo, X J
Abstract: A blade element momentum model for predicting the aerodynamic performance of dual-rotor wind turbines (DRWTs) as an aerodynamic design tool is introduced in this paper. The model considers the inter-rotor axial velocity reduction and the tangential velocity components in the front rotor's wake to model the inter-rotor velocity interferences for the inflow velocity as the input of the BEM theory. A DRWT with two NREL 5MW rotors is studied using the present model and CFD simulations. Results from the two methods show good agreements with each other in the trends of power, thrust, and aerodynamic loads on the blades despite the error in near-tip regions. The present DRWT configurations have lower optimum tip speed ratios and a wider range of high- CP speeds. The maximum efficiency of the present turbine is improved by only 5%, indicating that a dedicated blade design for DRWT aerodynamics is required to enhance power output and lower the aerodynamic loads.